Gravity-driven membrane (GDM) filtration of algae-polluted surface water. (August 2020) - Truttmann, Lars; Su, Yixi; Lee, Seonki; Burkhardt, Michael; Brynjólfsson, Sigurður; Chong, Tzyy Haur; Wu, Bing
Highlights: UF-GDM had higher flux than MF-GDM in treating algae-polluted lake water. Diatom cells caused more negative impacts on UF-GDM performance. Green algae had insignificant effects on UF-GDM performance. Presence of algal cells in feed water led to more reversible fouling of UF-GDM. Biopolymers were associated with UF-GDM membrane fouling. Abstract: This study compared the membrane performances and water quality of gravity-driven membrane (GDM) systems in treating algae-polluted lake water under different operation conditions (microfiltration (MF) vs. ultrafiltration (UF); Chlorella vulgaris (green algae) vs. Phaeodactylum tricornutum (diatom); different algal amounts in the lake water). The results showed the cake layer fouling was predominant in the UF-GDM systems, while irreversible fouling contributed majorly to the MF-GDM fouling. As a result, the UF-GDM systems achieved >1.5 time higher permeate flux compared to the MF-GDM systems in treating algae-polluted lake water. Compared to the green algae, the presence of the diatom cells in the feed water had more negative impacts on the UF permeate flux (increasing the cake layer resistance) and water quality (containing more low molecule weight neutrals). The analysis of cake layer foulants revealed that more aromatic protein-based biopolymers were accumulated on the membranes during filtration of algae-polluted lake water and the biopolymer amounts were almost linearly associated with membrane fouling potential of the GDM systems.